KOMBINASI EKSTRAK BAWANG DAN KUNYIT SEBAGAI OBAT ALTERNATIF HIPERKOLESTEROLEMIA - Yuni Alfianingsih; Intan Fazrin; Agma Permana; Ulfa Lutfiana Widyaningtyas; Tatik Ega Taviana Admasari; Dewi Masruroh (Universitas STRADA Indonesia, 2017)
Diseases caused hypercholesterolemia can be caused by the wrong diet, alcohol drinking habits and genetics. Plants around can be used for traditional treatments such garlic and turmeric. Garlic and turmeric serves to stabilize hiperkolestrol. Garlic has allisin and aliin content that can lower cholesterol levels, while turmeric is a kurkuminoid. The design study is Quasi-Experimental approach to pre and post test controlled group design. Data were tested by t-test. Results of statistical tests concluded that the significance <0.05 then H0 is rejected it means a difference between the first inspection and the fourth, in most comparisons doses used in this study. Yet another was concluded that the use of a dose ratio of 1: 1 can be significant lowering cholesterol. The most significant value is 0.009 which is obtained from the use of a dose 200 mg to 200 mg garlic extract and turmeric extract given treatment for 21 days.